Learning Creative Economy Empowerment through Optimizing Media Digital and Utilizing Inorganic Waste to Become Batik Patterned Chairs - Hidayatullah, Rizky; Suhono, Suhono; Irhamudin, Irhamudin; Hidayah, Yayuk; Sari, Yeasy Agustina; Haikal, Haikal (Bulletin of Science Education, 2024)
The aim of this assistance is to provide learning of training and assistance in optimizing digital marketing media through social media, such as Instagram, websites and Facebook. The second is to provide training and assistance in utilizing inorganic waste to make chairs with local batik motifs in Indonesia, training and assistance in introducing local batik in Indonesia as a brand in promoting batik patterned chair products. The method used Asset Based Community Development (ABCD) by maximizing asset potential. The results of this mitigation have achieved the target, that refers to low and medium hanging fruit, the subject of mitigation is the Waste Bank Community and Members of Pagar Nusa Metro City, the Waste Bank Community and the surrounding community have understood the condition of Smapah in Metro City and the risks or impacts arising from the pile up. Garbage is increasingly piling up in Metro City. The second is the reducing subject to understand theoretically and practically how to use inorganic waste such as aqua bottles, cloth, plastic into sofas or chairs with batik motifs. The third target is that Instagram business account owners can optimize and utilize digital media, such as Instagram as a one of the platforms for online digital marketing. At this stage, business Instagram users or marketing subjects understand how to optimize various features on Instagram and strategies for using those features, such as optimizing business Instagram profiles, determining posting schedules, optimizing hashtags, creating interesting content, creating contact and email buttons, or website, Optimizing Insights and Instagram stories, Optimizing Ads or Advertisements on Instagram. Keywords: Optimizing Media Digital, Utilizing Inorganic Waste, Learning Creative Economy